Pengaruh Perubahan Iklim terhadap Hidrograf Banjir di Kanal Banjir Timur Kota Semarang - Suripin, Suripin; Kurniani, Dwi (MEDIA KOMUNIKASI TEKNIK SIPIL, 2016)
East Flood Way is one of the rivers in Semarang City that often cause flooding. Flood water level in the East Flood Way is affected by the discharge of storm water runoff and tide (rob). Facts on the ground indicate that the flood water level in the canal tends to increase from year to year. One possible reason is the increased flood discharge associated with climate change, besides the impacts of land use changes. This study aims to analyze the impacts of climate change on rainfall characteristics and their effects on flood hydrograph in the East Flood Way. The study begins with the collection and analysis of historical rainfall data to get a change of rainfall characteristics over time. The flood hydrograph was then analysed by HEC HMS. The results showed that in the period of last 30 years annual rainfall and maximum daily rainfall tended to increase of 22.64 mm / year and 2.56 mm / year consecutively, while the number of rainy days tend to decrease of 4 days / year. As a result of changes in the characteristics of the rainfall, the flood discharge of East Flood Way is expected to increase in the range between the 15.10 m3/s (31.5%) for 2-year return period up to 32.28 m3/s (25.5 %) for 200-year return period.